New rules for sharing benefits from the use of digital sequence information - Halewood, Michael (Springer, 2024)
It is important for scientists engaged in genome editing to appreciate that the international community is currently engaged in highly dynamic negotiations to develop new rules for sharing benefits derived from the use of digital sequence information/genomic sequence data (DSI/GSD). Over the course of 10 years, this issue has grown in importance to the point where it is a key sticking point in at least four different United Nations fora. This paper examines why benefit-sharing from the use of DSI/GSD has become such an important topic, provides and overview of the current state of negotiations in key UN fora, and considers different potential outcomes.